Preparation method of composite filler with heat conduction and hydrophobic effects
By growing mesoporous silica in situ on the surface of hexagonal boron nitride powder and undergoing chemical bond coating modification, the problems of uneven dispersion of boron nitride in the coating and harsh storage conditions are solved, and the thermal conductivity and hydrophobic effects of the composite filler are achieved, and the process is simple and easy to perform.
Patent Information
- Application Number
- CN202411854097.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-11
AI Technical Summary
Hexagonal boron nitride is prone to clustering in coatings, affecting its dispersion uniformity and performance stability. At the same time, its application requires specific technologies and equipment, and the storage conditions are harsh.
Mesoporous silica is grown in situ on the surface of hexagonal boron nitride powder, and the end hydroxyl polysiloxane is used to condense with hydroxyl groups on mesoporous silica through chemical bonds, and coated and modified to form a composite filler with both thermal conductivity and hydrophobic effects.
The modified composite filler is uniformly dispersed in the resin, which improves the thermal conductivity and hydrophobicity of the coating, and is simple in process and is easy to develop in industrialization.
Smart Images

Figure CN119592101A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite functional fillers, and in particular relates to a method for preparing a composite filler having both heat conductive and hydrophobic effects. Background Art
[0002] Fillers play a vital role in coatings. They not only affect the physical and chemical properties of coatings, but also have a significant impact on the performance of coating films. The main functions of fillers in coatings include: reducing costs, improving coating properties, enhancing coating film properties, adjusting optical properties, providing special functions such as UV, antistatic or conductive, improving the storage performance of coatings, and increasing the hiding power of coatings.
[0003] Hexagonal boron nitride is a high-end functional filler and a two-dimensional material with unique physical and chemical properties. Its structure is similar to that of graphene, but it has different electronic properties. It has good high-temperature stability, wear resistance, corrosion resistance, thermal conductivity, electrical insulation, lubricity, non-wetting, and environmental protection. It can be used in heat-resistant coatings, anti-corrosion coatings and other fields. However, due to the surface passivation characteristics and poor wettability of boron nitride, it is easy to cluster when dispersed in the coating system. In addition, the application of boron nitride coatings may require specific techniques and equipment to ensure the uniformity and adhesion of the coating, and the coating with boron nitride needs to be stored under specific temperature and humidity conditions to maintain its performance. Summary of the invention
[0004] In order to solve the above technical problems, the present invention has developed a method for preparing a composite filler with both thermal conductivity and hydrophobicity using boron nitride as a matrix. The obtained composite filler can be applied to the field of functional coatings. The specific process of the preparation method is as follows: Step 1: Disperse the hexagonal boron nitride powder in anhydrous ethanol, ultrasonically disperse it for 0.5 to 2 hours by an ultrasonic disperser, then add hexadecyl trimethyl ammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water, adjust the system pH to 9 to 10, then stir at room temperature for 0.5 to 5 hours at a speed of 200 to 1000 rpm, and then transfer it to a polytetrafluoroethylene-lined autoclave, and the system reacts at a temperature range of 110°C to 140°C for 18 to 48 hours, and mesoporous silica grows on the surface of the hexagonal boron nitride powder through a hydrothermal reaction. The obtained solid product is separated from the remaining liquid by suction filtration, and the obtained powder is stirred in an ethanol solution at 60 to 80°C for 8 to 12 hours to remove hexadecyl trimethyl ammonium bromide. After filtering, the obtained powder is vacuum dried at 100°C to 120°C for 12 to 36 hours to obtain the mesoporous silica in-situ coated hexagonal boron nitride powder.
[0005] Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add terminal hydroxyl polysiloxane and a catalyst, stir at 40°C to 80°C for 4 to 8 hours, and the terminal hydroxyl polysiloxane and mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then washed with xylene multiple times, and finally dried in a vacuum oven at 60°C to 90°C for 12 to 24 hours. A composite filler with both thermal conductivity and hydrophobicity is obtained.
[0006] Preferably, the average particle size of the hexagonal boron nitride powder in step 1 is in the range of 6 microns to 13 microns.
[0007] Preferably, the concentration of the boron nitride dispersed in anhydrous ethanol in step 1 is 0.1 g / l to 20 g / l.
[0008] Preferably, the ultrasonic disperser described in step 1 has an ultrasonic frequency of 40 kHz and a power range of 50 W to 900 W.
[0009] Preferably, the mass ratio of the hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water in step 1 is in the range of: Hexagonal boron nitride powder 40wt%~60wt%; Hexadecyltrimethylammonium bromide 1wt%~5wt%; Ethyl orthosilicate 30wt%~50wt%; Silane coupling agent 1wt%~8wt%; Concentrated ammonia water 0.1wt%~0.3wt%.
[0010] Preferably, the silane coupling agent in step 1 is (3-epoxypropoxy)propyltrimethoxysilane or γ-aminopropyltriethoxysilane.
[0011] Preferably, the mesoporous silica in-situ coated hexagonal boron nitride powder described in step 2 is dispersed in a xylene solution, and its dispersion concentration is controlled at 1 g / l to 20 g / l.
[0012] Preferably, the mass ratio of the mesoporous silica in-situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane in step 2 is in the range of 40w% to 70w%: 30w to 60w%, and the mass of the catalyst used is 0.01wt% to 0.1wt% of the total mass of the mesoporous silica in-situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane.
[0013] Preferably, the viscosity of the hydroxy-terminated polysiloxane used in step 2 is in the range of 3000 centipoise to 100000 centipoise.
[0014] Preferably, the catalyst used in step 2 is dibutyltin dilaurate or stannous octoate.
[0015] A composite filler having both thermal conductivity and hydrophobic effects, wherein the composite filler is prepared by the above-mentioned preparation method.
[0016] A composite coating contains the composite filler prepared by the above preparation method.
[0017] The beneficial effects of the present invention are: 1. Utilizing the hydroxyl groups on the mesoporous silica grown in situ on the surface of hexagonal boron nitride, the hydroxy-terminated polysiloxane can be effectively connected by chemical bonds to coat and modify the surface of boron nitride; compared with traditional physical encapsulation, its modification effect is more stable and can effectively promote the uniform dispersion of fillers in the resin.
[0018] 2. The surface modification of hexagonal boron nitride by terminal hydroxyl polysiloxane gives the filler better hydrophobic properties due to its low surface tension properties.
[0019] 3. The preparation process adopted by the present invention is simple, does not require high temperature and high pressure operation, and is easier to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The overall morphology of the composite filler with both thermal conductivity and hydrophobicity prepared in Example 1 observed by scanning electron microscopy; Figure 2 The surface microstructure of the composite filler with both thermal conductivity and hydrophobicity prepared in Example 1 observed by scanning electron microscopy; Figure 3 The cross-sectional morphology of the epoxy composite coating doped with the composite filler having both thermal conductivity and hydrophobicity prepared in Example 1 is obtained by scanning electron microscopy; Figure 4 To compare the epoxy composite coating doped with ordinary hexagonal boron nitride and the composite filler prepared in Example 1 after salt spray corrosion; Figure 5 To compare the contact angle variation of epoxy composite coatings doped with common hexagonal boron nitride and the composite fillers prepared in Examples 1 to 4; Figure 6 To compare the thermal conductivity of epoxy composite coatings doped with common hexagonal boron nitride and the composite fillers prepared in Examples 1 to 4. DETAILED DESCRIPTION Example
[0021] A composite filler having both thermal conductivity and hydrophobicity is prepared, including the following processes: Step 1: Disperse the hexagonal boron nitride powder in anhydrous ethanol, ultrasonically disperse it for 0.5 hours using an ultrasonic disperser, then add hexadecyl trimethyl ammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water, adjust the system pH to 9, then stir at room temperature for 0.5 hours at a speed of 200 rpm, then transfer to a polytetrafluoroethylene-lined autoclave, and react the system at a temperature range of 110°C for 48 hours, and grow mesoporous silica on the surface of the hexagonal boron nitride powder through a hydrothermal reaction. The obtained solid product is separated from the remaining liquid by suction filtration, and the obtained powder is stirred in an ethanol solution at 60°C for 12 hours to remove hexadecyl trimethyl ammonium bromide. After filtering, the obtained powder is vacuum dried at 100°C for 36 hours to obtain the in-situ hexagonal boron nitride powder coated with mesoporous silica.
[0022] Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add hydroxyl-terminated polysiloxane and a catalyst, stir at 40°C for 8 hours, and the hydroxyl-terminated polysiloxane and mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then continuously washed with xylene, and finally dried in a vacuum oven at 60°C for 24 hours. A composite filler with both thermal conductivity and hydrophobicity is obtained.
[0023] Wherein, in step 1, the average particle size of hexagonal boron nitride powder is 6 microns; the concentration of boron nitride dispersed in anhydrous ethanol is 0.1 g / l; the ultrasonic frequency of the ultrasonic disperser is 40 kHz, and the power is 900 W; the silane coupling agent is γ-aminopropyltriethoxysilane. The mass ratio of hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water is in the range of: Hexagonal boron nitride powder 40wt%; Hexadecyltrimethylammonium bromide 1.7wt%; Ethyl orthosilicate 50wt%; Silane coupling agent 8wt%; Concentrated ammonia water 0.3wt%.
[0024] In step 2, mesoporous silica in situ coated hexagonal boron nitride powder is dispersed in a xylene solution, and its dispersion concentration is controlled at 1 g / l; the mass ratio of mesoporous silica in situ coated hexagonal boron nitride powder to terminal hydroxyl polysiloxane is in the range of 40w%:60w%, the mass of the catalyst used is 0.1wt% of the total mass of the mesoporous silica in situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane; the viscosity of the terminal hydroxyl polysiloxane is 3000 centipoise; the catalyst used is dibutyltin dilaurate. Example
[0025] A composite filler having both thermal conductivity and hydrophobicity is prepared, including the following processes: Step 1: Disperse the hexagonal boron nitride powder in anhydrous ethanol, ultrasonically disperse it for 1 hour by an ultrasonic disperser, then add hexadecyl trimethyl ammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water, adjust the pH value of the system to 10, then stir at room temperature for 1 hour at a speed of 500 rpm, and then transfer it to a polytetrafluoroethylene-lined autoclave. The system reacts for 36 hours at a temperature range of 120°C, and mesoporous silica grows on the surface of the hexagonal boron nitride powder through a hydrothermal reaction. The obtained solid product is separated from the remaining liquid by suction filtration, and the obtained powder is stirred in an ethanol solution at 65°C for 10 hours to remove hexadecyl trimethyl ammonium bromide. After filtering, the obtained powder is vacuum dried at 105°C for 24 hours to obtain the in-situ hexagonal boron nitride powder coated with mesoporous silica.
[0026] Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add hydroxyl-terminated polysiloxane and a catalyst, stir at 50°C for 7 hours, and the hydroxyl-terminated polysiloxane and mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then continuously washed with xylene, and finally dried in a vacuum oven at 70°C for 18 hours. A composite filler with both thermal conductivity and hydrophobicity is obtained.
[0027] Wherein, in step 1, the average particle size of hexagonal boron nitride powder is 8 microns; the concentration of boron nitride dispersed in anhydrous ethanol is 5g / l; the ultrasonic frequency of the ultrasonic disperser is 40kHz, and the power is 500W; the silane coupling agent is γ-aminopropyltriethoxysilane. The mass ratio of hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water is in the range of: Hexagonal boron nitride powder 51.85wt%; Hexadecyltrimethylammonium bromide 2wt%; Ethyl orthosilicate 45wt%; Silane coupling agent 1wt%; Concentrated ammonia water 0.15wt%.
[0028] In step 2, mesoporous silica in situ coated hexagonal boron nitride powder is dispersed in a xylene solution, and its dispersion concentration is controlled at 5 g / l; the mass ratio of mesoporous silica in situ coated hexagonal boron nitride powder to terminal hydroxyl polysiloxane is in the range of 50w%:50w%; the mass of the catalyst used is 0.08wt% of the total mass of the mesoporous silica in situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane; the viscosity of the terminal hydroxyl polysiloxane used is 10,000 centipoise; the catalyst used is dibutyltin dilaurate. Example
[0029] A composite filler having both thermal conductivity and hydrophobicity is prepared, including the following processes: Step 1: Disperse the hexagonal boron nitride powder in anhydrous ethanol, ultrasonically disperse it for 1.5 hours using an ultrasonic disperser, then add hexadecyl trimethyl ammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water, adjust the system pH to 9, then stir at room temperature for 2.5 hours at 800 rpm, then transfer to a polytetrafluoroethylene-lined autoclave, react the system at a temperature range of 130°C for 24 hours, and grow mesoporous silica on the surface of the hexagonal boron nitride powder through a hydrothermal reaction. The obtained solid product is separated from the remaining liquid by suction filtration, and the obtained powder is stirred in an ethanol solution at 75°C for 9 hours to remove hexadecyl trimethyl ammonium bromide. After filtration, the obtained powder is vacuum dried at 110°C for 18 hours to obtain the in-situ hexagonal boron nitride powder coated with mesoporous silica.
[0030] Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add hydroxyl-terminated polysiloxane and a catalyst, stir at 60°C for 5 hours, and the hydroxyl-terminated polysiloxane and mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then continuously washed with xylene, and finally dried in a vacuum oven at 80°C for 15 hours. A composite filler with both thermal conductivity and hydrophobicity is obtained.
[0031] Wherein, in step 1, the average particle size of hexagonal boron nitride powder is 10 microns; the concentration of boron nitride dispersed in anhydrous ethanol is 10g / l; the ultrasonic frequency of the ultrasonic disperser is 40kHz, and the power is 200W; the alkane coupling agent is (3-epoxypropoxy)propyltrimethoxysilane. The mass ratio of hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water is in the range of: Hexagonal boron nitride powder 57.75wt%; Hexadecyltrimethylammonium bromide 5wt%; Ethyl orthosilicate 30wt%; Silane coupling agent 7wt%; Concentrated ammonia water 0.25wt%.
[0032] In step 2, mesoporous silica in situ coated hexagonal boron nitride powder is dispersed in a xylene solution, and its dispersion concentration is controlled at 10 g / l; the mass ratio of mesoporous silica in situ coated hexagonal boron nitride powder to terminal hydroxyl polysiloxane is in the range of 60w%:40w%, the mass of the catalyst used is 0.05wt% of the total mass of the mesoporous silica in situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane; the viscosity of the terminal hydroxyl polysiloxane used is 50,000 centipoise; the catalyst used is stannous octoate. Example
[0033] A composite filler having both thermal conductivity and hydrophobicity is prepared, including the following processes: Step 1: Disperse the hexagonal boron nitride powder in anhydrous ethanol, ultrasonically disperse it for 2 hours in an ultrasonic disperser, then add hexadecyl trimethyl ammonium bromide, tetraethyl orthosilicate, silane coupling agent, and concentrated ammonia water, adjust the pH value of the system to 10, and then stir at room temperature for 5 hours at a speed of 1000 rpm, and then transfer it to a polytetrafluoroethylene-lined autoclave, and the system reacts for 18 hours at a temperature range of 140°C, and mesoporous silica grows on the surface of the hexagonal boron nitride powder through a hydrothermal reaction. The obtained solid product is separated from the remaining liquid by suction filtration, and the obtained powder is stirred in an ethanol solution at 80°C for 8 hours to remove hexadecyl trimethyl ammonium bromide. After filtering, the obtained powder is vacuum dried at 120°C for 12 hours to obtain the in-situ hexagonal boron nitride powder coated with mesoporous silica.
[0034] Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add hydroxyl-terminated polysiloxane and a catalyst, stir at 80°C for 4 hours, and the hydroxyl-terminated polysiloxane and mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then continuously washed with xylene, and finally dried in a vacuum oven at 90°C for 12 hours. A composite filler with both thermal conductivity and hydrophobicity is obtained.
[0035] Wherein, in step 1, the average particle size of hexagonal boron nitride powder is 13 microns; the concentration of boron nitride dispersed in anhydrous ethanol is 20g / l; the ultrasonic frequency of the ultrasonic disperser is 40kHz, and the power is 50W; the silane coupling agent is (3-epoxypropoxy)propyltrimethoxysilane. The mass ratio of hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water is in the range of: Hexagonal boron nitride powder 60wt%; Hexadecyltrimethylammonium bromide 1wt%; Ethyl orthosilicate 32.9wt%; Silane coupling agent 6wt%; Concentrated ammonia water 0.1wt%.
[0036] In step 2, mesoporous silica in situ coated hexagonal boron nitride powder is dispersed in a xylene solution, and its dispersion concentration is controlled at 20 g / l; the mass ratio of mesoporous silica in situ coated hexagonal boron nitride powder to terminal hydroxyl polysiloxane is in the range of 70w%:30w%, the mass of the catalyst used is 0.01wt% of the total mass of the mesoporous silica in situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane; the viscosity of the terminal hydroxyl polysiloxane used is 100000 centipoise; the catalyst used is dibutyltin dilaurate. Example
[0037] According to the raw material ratio shown in Table 1, a coating doped with the composite filler prepared by the present invention having both thermal conductivity and hydrophobic effects is prepared.
[0038] Table 1. Paint preparation scheme of composite fillers prepared according to the present invention The defoamer may be BYK-070 and BYK-8800 from BYK, or TEGO® Foamex N from Tego. The leveling agent may be BYK-333 from BYK. The wetting and dispersing agent may be A-5088 and A-5044 from FKA.
[0039] The preparation scheme is as follows: first, add epoxy resin and wetting dispersant to half of butyl acetate, stir at 800 rpm for 10 minutes, and stir evenly. Then gradually add the composite filler prepared by the present invention, stir at 1200 rpm for 1 hour, and then add leveling agent, defoamer and remaining butyl acetate solvent. Stir at 400 rpm for 10 minutes and mix evenly. Before coating the board, add polyamide curing agent 651 designed in Table 1, stir evenly to obtain the designed composite coating, and each coating is defined as Example 1 coating, Example 2 coating, Example 3 coating, and Example 4 coating. It is applied to the surface of the metal substrate by brushing, spraying or rolling, and its various properties are tested after being placed for 7 days.
[0040] In addition, in order to compare the actual application effect of the prepared composite filler with both thermal conductivity and hydrophobicity, the present invention also selects the hexagonal boron nitride used in Example 1, and prepares a composite coating according to the experimental formula and operating precautions shown in Table 1, which is defined as a comparative coating.
[0041] The specific performance indicators of the coating prepared based on the composite filler prepared by the present invention and the coating prepared by the comparative example coating are shown in Table 2 below: Table 2. Performance indicators of composite coatings and their cured coatings Test items and standards Example 1 Coating Example 2 Coating Example 3 Coating Example 4 Coating Comparative Example 1 Coating State of paint in container After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps After stirring, it is smooth and has no lumps Paint drying time (surface drying) / h <1 <1 <1 <1 <1 Paint drying time (actual drying) / h <24 <24 <24 <24 <24 Initial drying crack resistance of coating No cracks No cracks No cracks No cracks No cracks Coating pencil hardness (GB / T6739-2006) 2H H HB 2H 2H Coating flexibility (GB / T1731-1993) 1mm 1mm 1mm 1mm 1mm Cross-cut adhesion of coatings (GB / T 9286-1998) Level 0 Level 0 Level 0 Level 0 Level 0 Impact resistance of coating film (GB / T 1732-1993) Forward / reverse flush Forward / reverse flush Forward / reverse flush Forward / reverse flush Forward / reverse flush Coating contact angle 122° 113° 108° 104° 85° <![CDATA[Coating through-surface (K ⊥ ) Thermal conductivity]]> 0.39 0.29 0.28 0.25 0.16 <![CDATA[Coating parallel plane (K ∥ ) Thermal conductivity]]> 0.75 0.41 0.40 0.15 0.05 Salt spray resistance of coating (ASTM B117) >500h No blistering, obvious deterioration or softening of the coating >450h No blistering, obvious deterioration or softening of the coating >400h No blistering, obvious deterioration or softening of the coating >500h No blistering, obvious deterioration or softening of the coating >200h No blistering, obvious deterioration or softening of the coating Coating moisture and heat resistance / h (GB / T 1740-2007) 500, no delamination or shedding 500, no delamination or shedding 500, no delamination or shedding 500, no delamination or shedding 300, no delamination or shedding Figure 1 The overall morphology of the composite filler with both thermal conductivity and hydrophobicity prepared in Example 1 observed by scanning electron microscopy; Figure 2 The surface microstructure of the composite filler with both thermal conductivity and hydrophobicity prepared in Example 1 observed by scanning electron microscopy; since the surface of the boron nitride is modified, the originally flat and smooth surface of the hexagonal boron nitride becomes rough and uneven; this is conducive to promoting the effective dispersion of the filler in the resin.
[0042] Figure 3 The cross-sectional morphology of the epoxy composite coating doped with the composite filler having both thermal conductivity and hydrophobicity prepared in Example 1 is shown by scanning electron microscopy. Due to the modification of the filler surface, it can be evenly dispersed in the coating. On the one hand, a maze effect is formed to inhibit the occurrence of corrosion; on the other hand, the fillers are dispersed and contacted with each other, which is conducive to forming an effective heat conduction channel.
[0043] Figure 4 To compare the epoxy composite coating doped with ordinary hexagonal boron nitride (above) and the composite filler prepared in Example 1 (below) after salt spray corrosion, it can be seen from the comparison between the two that the coating with the sample prepared in Example 1 has higher salt spray corrosion resistance than the coating with ordinary hexagonal boron nitride; Figure 5 To compare the contact angle variation of epoxy composite coatings doped with common hexagonal boron nitride and the composite fillers prepared in Examples 1 to 4, common hexagonal boron nitride can effectively reduce the surface tension of the prepared coating and improve the hydrophobicity of the coating surface after modification; Figure 6 To compare the thermal conductivity of epoxy composite coatings doped with common hexagonal boron nitride and the composite fillers prepared in Examples 1 to 4, the surface modification of hexagonal boron nitride will not destroy the thermal conductivity of the coating. On the contrary, due to the effective dispersion of boron nitride, the thermal conductivity of the coating can be promoted.
[0044] The present invention is not limited to the above-mentioned specific implementation modes. For ordinary technicians in this field, various changes made based on the above-mentioned conception without creative work all fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite filler having both thermal conductivity and hydrophobicity, characterized in that: The preparation process includes the following: Step 1, dispersing hexagonal boron nitride powder in anhydrous ethanol, ultrasonically dispersing it for 0.5 to 2 hours by an ultrasonic disperser, then adding hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water, adjusting the pH value of the system to 9 to 10, and then stirring at room temperature for 0.5 to 5 hours at a speed of 200 to 1000 rpm, and then transferring it to a high-pressure reactor, and the system reacts at a temperature range of 110° C. to 140° C. for 18 to 48 hours, and mesoporous silica grows on the surface of the hexagonal boron nitride powder through a hydrothermal reaction; separating the obtained solid product from the remaining liquid by suction filtration, stirring the obtained powder in an ethanol solution at 60 to 80° C. for 8 to 12 hours to remove hexadecyltrimethylammonium bromide, and after filtering, the obtained powder is vacuum dried at 100° C. to 120° C. for 12 to 36 hours to obtain mesoporous silica in-situ coated hexagonal boron nitride powder; Step 2: Disperse the mesoporous silica in-situ coated hexagonal boron nitride powder prepared in step 1 in a xylene solution, then add terminal hydroxyl polysiloxane and a catalyst, and stir at 40°C to 80°C for 4 to 8 hours. The terminal hydroxyl polysiloxane and the mesoporous silica in-situ coated hexagonal boron nitride powder undergo a condensation reaction with the hydroxyl groups on the mesoporous silica, and are coated and modified using chemical bonds. The product after the reaction is first filtered, then washed with xylene for multiple times, and finally dried in a vacuum oven at 60°C to 90°C for 12 to 24 hours. A composite filler having both thermal conductivity and hydrophobicity is obtained.
2. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The concentration of the boron nitride dispersed in anhydrous ethanol in step 1 is 0.1 g / l to 20 g / l.
3. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The mass ratio of the hexagonal boron nitride powder, hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, silane coupling agent and concentrated ammonia water described in step 1 is: Hexagonal boron nitride powder 40wt%~60wt%; Hexadecyltrimethylammonium bromide 1wt%~5wt%; Ethyl orthosilicate 30wt%~50wt%; Silane coupling agent 1wt%~8wt%; Concentrated ammonia water 0.1wt%~0.3wt%.
4. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The silane coupling agent described in step 1 is (3-epoxypropoxy)propyltrimethoxysilane or γ-aminopropyltriethoxysilane.
5. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The mesoporous silica in-situ coated hexagonal boron nitride powder described in step 2 is dispersed in a xylene solution, and its dispersion concentration is controlled at 1 g / l to 20 g / l.
6. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The mass ratio of the mesoporous silica in-situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane in step 2 is: 40w%~70w%:30w~60w%, and the mass of the catalyst used is 0.01wt%~0.1wt% of the total mass of the mesoporous silica in-situ coated hexagonal boron nitride powder and the terminal hydroxyl polysiloxane.
7. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The viscosity of the hydroxy-terminated polysiloxane used in step 2 ranges from 3000 centipoise to 100000 centipoise.
8. The method for preparing a composite filler having both thermal conductivity and hydrophobicity according to claim 1, characterized in that: The catalyst used in step 2 is dibutyltin dilaurate or stannous octoate.
9. A composite filler having both thermal conductivity and hydrophobicity, characterized in that: The composite filler is prepared by the preparation method described in claim 1.
10. A composite coating, characterized in that: The composite coating contains the composite filler prepared by the preparation method according to claim 1.
Citation Information
Cited By
High-performance soluble polytetrafluoroethylene material and preparation method thereof
CN120623684A